2009
DOI: 10.1007/bf03086267
|View full text |Cite
|
Sign up to set email alerts
|

Acute myocardial infarction complicating subarachnoid haemorrhage

Abstract: An acute myocardial infarction is a rare complication of a subarachnoid haemorrhage. The combination of these two conditions imposes important treatment dilemmas. We describe two patients with this combination of life-threatening conditions. Patient 1 was treated with emergency percutaneous coronary intervention followed by clipping of the anterior communicating artery aneurysm. Six months after discharge the patient's memory and orientation had almost completely recovered. Patient 2 was treated with aspirin u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…Only two other cases of subarachnoid haemorrhage with obstructive coronary arteries have been reported and in both cases, the predominant symptom was headaches with meningism. 2 This gentleman had no neurological signs and the predominant symptom was chest pain.…”
Section: Discussionmentioning
confidence: 98%
“…Only two other cases of subarachnoid haemorrhage with obstructive coronary arteries have been reported and in both cases, the predominant symptom was headaches with meningism. 2 This gentleman had no neurological signs and the predominant symptom was chest pain.…”
Section: Discussionmentioning
confidence: 98%
“…A review of the literature showed only three cases of concomitant MI and SAH in patients with a decreased level of consciousness. [7,9] In Tan et al report, the patient admitted with cardiac manifestation and then developed SAH. However, they believe that SAH was the initial event that causes secondary coronary plaque rupture.…”
Section: Discussionmentioning
confidence: 99%
“…Platelets and their coagulation factors play a significant role in the development of clinical vasospasm. [9] ey showed that antiplatelet therapy could be started as soon as 72 h after SAH or after coiling of the aneurysm. [9] Nagahama et al showed that treatment with an antiplatelet agent led to a decrease of vasospasm and poor outcome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[3][4][5][6][7][8][9][10][11] The nine cases have been selected based on originality and potential educational interest to the reader. Topics of the case histories are the various manifestations of ischaemic heart disease varying from drug-induced myocardial infarction to aneurysms of coronary artery bypass grafts.…”
mentioning
confidence: 99%